2019
DOI: 10.1159/000499862
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Disease Awareness and Knowledge among Survivors ofAcute Kidney Injury

Abstract: Background: Acute kidney injury (AKI) survivors are at risk for chronic kidney disease, recurrent AKI, and cardiovascular disease. The transition from hospital to ambulatory care is an opportunity to reduce these sequelae by launching self-care plans through effective patient education. How well AKI survivors are informationally prepared to apply kidney-specific self-care is unknown. The purpose of this study was to identify awareness and disease-specific knowledge among AKI survivors. Methods: We performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 52 publications
0
27
1
2
Order By: Relevance
“…Patient characteristics by treatment group were similar, except those in the early nephrologist arm were slightly younger (mean6SD, 64610 versus 67612 years), were less likely to have preexisting heart failure (18% versus 30%) and hypertension (56% versus 78%), and had a shorter length of hospital stay (median [IQR], 11 [7][8][9][10][11][12][13][14][15][16][17][18][19] versus 16 [10][11][12][13][14][15][16][17][18][19][20][21][22] days). They were also more likely to have experienced KDIGO stage 3 AKI (68% versus 54%; Table 1).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Patient characteristics by treatment group were similar, except those in the early nephrologist arm were slightly younger (mean6SD, 64610 versus 67612 years), were less likely to have preexisting heart failure (18% versus 30%) and hypertension (56% versus 78%), and had a shorter length of hospital stay (median [IQR], 11 [7][8][9][10][11][12][13][14][15][16][17][18][19] versus 16 [10][11][12][13][14][15][16][17][18][19][20][21][22] days). They were also more likely to have experienced KDIGO stage 3 AKI (68% versus 54%; Table 1).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Communication between health care providers and patients is also important. A recent observational study of 137 patients with moderate to severe AKI showed that 80% of patients were unaware of their diagnosis (71), and it is estimated that less than half of hospital discharge documentation records AKI (72,73). There is, therefore, a significant opportunity to develop and test different approaches to post-AKI care, as well as to work to improve recognition and communication.…”
Section: Aki Aftercarementioning
confidence: 99%
“…Considering the high incidence of AKI and improvements in short-term survival (74), these long-term sequelae of AKI present a major unmet clinical need, with no proven interventions or data to inform optimal care provision. Patients often receive no follow-up after hospital discharge (16), and they often do not realize that they have had AKI (71,75). The evidence base describing the long-term sequelae of AKI continues to grow, adding to our understanding and increasing awareness of these issues.…”
Section: Conclusion and Areas Of Uncertaintymentioning
confidence: 99%
“…Surprisingly, 80% of AKI survivors were unaware of their condition by the time of discharge, and 21% were unaware of their AKI diagnosis at the first AKI Clinic visit. 5,6 The AKI survivors were also shown to be at higher risk for rehospitalization than their counterparts without AKI. A population-based study showed that 18% of AKI survivors were readmitted within the first 30 days of discharge.…”
Section: Discussionmentioning
confidence: 99%